Designing a Midterm Reading Test for Junior High School Students in Semarang: A Practical Experience of a Master Student in TESOL - Waliyadin Waliyadin (Universitas Islam Negeri Walisongo Semarang, 2019)
Designing a test is an uneasy task. It is proven by the fact that many teachers find difficulties in designing a good test. The present article attempts to review the English school exam in Indonesia and present an example of the test design of a midterm reading test for junior high school students in Semarang. To this end, firstly, a sample of test script of the school exam for JHS students in Semarang in the academic year 2017/2018 was reviewed. The review of the test shows that creating a good quality of test items still become a concern for English teachers as they made some grammatical errors. Consecutively, a midterm reading test was also designed and administered in a junior high school in Semarang, Central Java. Then, the test designed was evaluated by considering the validity, reliability, and practicality as suggested by (Brown Abeywickrama, 2010). The administration of the test and evaluation show some weaknesses; therefore, the suggestions for the betterment of the test design are also made, such as revising some test items with a very low facility index and negative discrimination index. This study implicates pedagogically the teachers to train students on how to summarize and paraphrase since these skills underrepresented.